KESULITAN DAN HAMBATAN SISWA SAAT PEMBELAJARAN DARING SELAMA PANDEMI COVID-19 BERDASARKAN GENDER - Arini Pratiwi Putri; Risma Amelia (HISTOGRAM: Jurnal Pendidikan Matematika, 2021)
After the pandemic entered Indonesia, the Indonesian government has adopted a variety of methods to reduce the spread of the coronavirus, one of which is implementing a policy of physical distance. These policies limit the speed of development in various areas of life, one of which is the field of education, which is implemented through the distance learning (PJJ). The purpose of this research is to analyze the difficulties and obstacles that students face in the online learning process and their solutions. The research method used is a descriptive qualitative research method. The study was conducted in August and the number of respondents was 77 students in Class VII SMPN 3 Lembang, including 38 female students and 39 male students. The results of this study show that male and female students have almost the same difficulties and obstacles in online learning, but female students are more likely to encounter these difficulties because it is difficult for female students to concentrate on online learning.